Nubuatan Yehezkiel Tentang Kebangkitan Israel Dalam Perspektif Kristen Berdasarkan Yehezkiel 37:1-14 - Periman Jaya Lahagu; Sandra Rosiana Tapilaha (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The vision of passing from death to life is a glorious awakening. It is something that nature completely ignores, totally contrary to how it works (une privatione ad habitum non datur regressus-no way without ownership). Interestingly, the book of Ezekiel shows an unusual hope. In a valley full of human bones, God asked, "Can these bones rise again?" " Impossible! However, Ezekiel knows that nothing is impossible in God's hands. This paper uses qualitative research methods with a literary approach to present problems as well as analyze and collect data. With this in mind, the writer wants to discuss a number of things related to the text of Ezekiel 37 :1-14 itself. The main problem being considered is how to interpret the passage Ezekiel. 37:1-14. The conclusion is that through the text of Ezekiel 37:1-14, God actually wants to convey promises and messages of hope through Ezekiel. Text it mentions that Ezekiel saw a vision of dry bones in the valley, which was interpreted as a promise to save the Israelites.